Carcass Characteristics of Broiler Chicken Supplemented With Detoxifying Microbial Enzymes to Ameliorate Feed Toxins - Senthilkumar, S.; Janani, S. R.; Prabhakaran, K. P.; Vasanthakumar, P.; Purushothaman, M. R.; Chandrasekaran, D. (Journal of Meat Science, 2019)
A feeding trial was conducted to find out the carcass characteristics of broiler chicken by supplementing the detoxifying microbial en zymes (DME) on feed toxins. 420 number of day-old male broiler chicks were divided into fourteen groups 30 birds in each (42 days).  Treatment groups T1 and T2 were healthy control and positive control, respectively, T3 received naturally mycotoxin contaminated  feed at field level, T4 received naturally mycotoxin contaminated feed at field level +DME at 250g/ton of feed, T5 received naturally  contaminated feed with clostridium spp.,T6 received naturally contaminated feed with clostridium spp.+ DME at 250g/ ton of feed,  T7 received naturally contaminated feed with E.coli, T8 received naturally contaminated feed with E.coli + DME at 250g/ton of feed,  T9 infected with clostridium spp on day 8th, T10 infected with clostridium sp. on day 8th + DME at 250g/ton of feed, T11 infected  with E.coli on day 8th, T12 infected with E.coli on day 8th + DME at 250g/ton of feed, T13 received mycotoxin contaminated feed  inoculated with clostridium spp. and E.coli from day 8th, T14 received mycotoxin contaminated feed inoculated Clostridium spp. and  E.coli from day 8th + DME at 250g/ton of feed. At the end of 42nd day, six birds per treatment group were selected randomly and  slaughtered for slaughter studies such as carcass weight, dressing percentage, weight of organs such as liver, kidney, heart, gizzard, spleen,  thymus, bursa of fabricious, lungs, tibia and length of intestine were measured. The dressing percentage, weight of heart, spleen and  thymus do not differ significantly (P≥0.05), where as live body weight, weight of carcass, liver, kidney, gizzard, bursa of fabricious, lungs,  tibia and intestinal length significantly differed (P≤0.05) between treatment groups when compared to control diet. It could be concluded  that detoxifying microbial enzymes supplementation influenced the carcass characteristics and organ weight in broilers might be due to  detoxifying effect of DME against feed and other toxins.
Keywords: Broiler; Detoxifying microbial enzymes; Mycotoxin; Carcass characteristics; E.coli; Clostridium spp